CGFS‐type glutaredoxin mutations reduce tolerance to multiple abiotic stresses in tomato. Issue 3 (23rd August 2021) - Kakeshpour, Tayebeh; Tamang, Tej Man; Motolai, Gergely; Fleming, Zachary Wayne; Park, Jung‐Eun; Wu, Qingyu; Park, Sunghun
Abstract: Sessile organisms such as plants have adopted diverse reactive oxygen species (ROS) scavenging mechanisms to mitigate damage under abiotic stress conditions. Though CGFS‐type glutaredoxin ( GRX ) genes are important regulators of ROS homeostasis, each of their functions in crop plants have not yet been well understood. We performed a targeted mutagenesis analysis of four CGFS‐type GRXs ( SlGRXS14, SlGRXS15, SlGRXS16, and SlGRXS17 ) in tomato plants ( Solanum lycopersicum ) using a multiplex clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 system and found that Slgrxs mutants were more sensitive to various abiotic stresses compared with the wild‐type tomatoes. Slgrxs15 mutants were embryonic lethal. Single, double, and triple combinations of Slgrxs14, 16, and 17 mutants were examined under heat, chilling, drought, heavy metal toxicity, nutrient deficiency, and short photoperiod stresses. Slgrxs14 and 17 mutants showed hypersensitivity to almost all stresses while Slgrxs16 mutants were affected by chilling stress and showed milder sensitivity to other stresses. Additionally, Slgrxs14 and 17 mutants showed delayed flowering time. Our results indicate that the CGFS‐type SlGRXs have specific roles against abiotic stresses, providing valuable resources to develop tomato and, possibly, other crop species that are tolerant to multiple abiotic stresses by genetic engineering.